Postcolonial analysis of educational language policies of Ireland, Singapore, and Malaysia - Zuzanna Grala (LingBaW)
The aim of this paper is to compare the educational language policing in Ireland, Singapore, and Malaysia. While distant geographically, the three countries experience similar linguistic processes when it comes to anglicisation, and propose different solutions to the issue of balancing linguistic rights, and promotion of English as the language of globalisation.